The impact of international law on the emergence of constitutions (Al-Mansour Journal, 2025)
The juristic consensus is that there four ways and methods for drafting Constitutions according to the circumstances that the state is going through there are the non-democratic methods. Which are represented by the grant and the contract, which are very old methods that are no longer used in drafting constitution, and there are the democratic methods, namely the constitutional referendum, which are methods that are compatible with the principles of democracy. however, after the emergence of the importance of international treaties in establishing the constitution of some countries that are going through exceptional circumstances of war and occupation, as the case of federal union, here it became necessary for constitutional scholars to acknowledge the existence of a fifth method for establishing constitutions, which is the method of international treaties.
Keywords: constitution; international law; emergence; constitutional; Unconstitutional.